2018
DOI: 10.20319/pijss.2018.43.224237
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Factors to Promote Students’ Interest and Involvement in Teaching-Learning English

Abstract: There are many problems in English language teaching as Second Language Learning. Among them, the most common problem found in students is lack of motivation and lack of student's interest. To be effective teaching and learning, student's emotion and tendency is necessary. As teacher understands how important the motivation and their interest are, various kinds of teaching methods and strategies have been applying in the foreign language educational field.Therefore, this paper suggests how to arouse the studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…This indicates that they are less motivated or have low motivation in learning English. The results of this study are in line with the results of the research done by Win [31] who found that motivation is a common problem in teaching-learning English. However, the results of this study are in contrast with the expected learning process.…”
Section: Figure 6 the Students' Less Motivation In Learning Englishsupporting
confidence: 91%
“…This indicates that they are less motivated or have low motivation in learning English. The results of this study are in line with the results of the research done by Win [31] who found that motivation is a common problem in teaching-learning English. However, the results of this study are in contrast with the expected learning process.…”
Section: Figure 6 the Students' Less Motivation In Learning Englishsupporting
confidence: 91%
“…Furthermore, this can help learners to discover their talents and interests (Flutterman, 2016), and to release the stress from learning in the required courses while developing specific personal skills (Marcu, 2020). In terms of English teaching and learning, Win (2018) explained that if the course contents match the learners' interests; namely, daily routine and align with their language proficiency levels, it will increase learner motivation, attentiveness in class, and speed up the learning process because they are eager to participate in the learning activities (Spolsky, 1990). This can ultimately improve their language acquisition success (Harackiewicz et al, 2016;Reeves, 2011).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Moreover, he claims that it is tough to achieve effective learning without motivation. Although the students have surprising language acquisition skills, without motivation they can hardly achieve success in learning a second language (Win, 2018).…”
Section: Motivationmentioning
confidence: 99%
“…Most of the teenagers are interested in learning the languages, especially English. According to Win (2018), the learners' interest in learning the English language is the most important factor. If there is a strong desire to learn the English language, the results will be effective and efficient (Saroh, 2019).…”
Section: Introductionmentioning
confidence: 99%